A Neglected Additament: Peirce on Logic, Cosmology, and the Reality of God - Schmidt, Jon Alan (Signs - International Journal of Semiotics, 2018)
Two different versions of the ending of the first additament to C. S. Peirce’s 1908 article, "A Neglected Argument for the Reality of God," appear in the Collected Papers but were omitted from The Essential Peirce. In one, he linked the hypothesis of God’s Reality to his entire theory of logic as semeiotic, claiming that proving the latter would also prove the former. In the other, he offered a final outline of his cosmology, in which the Reality of God as Ens necessarium is indispensable to both the origin and order of our existing universe of Signs. Exploring these passages, as well as the unpublished manuscript drafts of the article, provides important insights into the key concepts of instinct and continuity within Peirce’s comprehensive system of thought.